Anna Karenina i Arktis: Tekst og landskap i Aritha van Herks Places Far From Ellesmere - Janicke Stensvaag Kaasa (Norsk Litteraturvitenskapelig Tidsskrift)
Anna Karenina in the Arctic: Text and Landscape in Aritha van Herk’s Places Far From Ellesmere The Arctic is an imagined space as much as a geographical place; our ideas and understanding of the region are based both in the fictional and the factual. Aritha van Herk’s Places Far From Ellesmere (1990) combines multiple genres in its experimental rendering of the author’s journey to the Canadian north, thus touching upon the issues of genre and the boundaries, or rather the lack of such boundaries, between the fictional and the factual in the literature of the Arctic. The article examines how van Herk’s text contests the genre conventions of exploration narratives through the traveller’s self-representation and by making Anna Karenina a key text in the account of her journey. These features, the article argues, are decisive to van Herk’s feminist critique of Tolstoy’s novel, as well as of exploration writing on the Arctic generally, and also point to the recurring issue of fact and fiction in the literature of the Arctic.